Islamic Work Ethic and Employee Performance: The Role of Job Satisfaction as a Mediator - Amaliasita, Mahsa; Astuti, Rini Juni (UNISSULA, 2023)
This study examines the direct influence of Islamic work ethic on employee performance. This study also investigates the role of job satisfaction as a mediation variable in the relationship between Islamic work ethic and employee performance variables. This study involved 69 respondents as samples that were determined using a data collection method, namely purposive sampling, and using a software, namely SmartPLS version 3.0, to employ partial least square (PLS). The empirical results of this study found that Islamic work ethic significantly influences employee performance. Meanwhile, job satisfaction can significantly mediate the relationship between Islamic work ethic and employee performance. Finally, this study discusses the implications, limitations, and further research.